Hydrochemical characteristics and groundwater quality assessment in Krishnagiri district, Tamilnadu, India - Manikandan, S.; Chidambaram, S.; Prasanna, Mohan Viswanathan; Thivya, C.; Karmegam, U. (CAFET-INNOVA Technical Society, Hyderabad, India, 2011)
The hydrochemical characteristics of groundwater in Krishnagiri district, Tamilnadu have been evaluated based on different indices for drinking, irrigation and industrial uses. Groundwater samples were collected from 34 boreholes and analyzed for chemical parameters. The abundance of the major ions is in order of: Na + > Mg 2+> Ca 2+ > K + and HCO 3-> Cl -> NO 3-> SO 42-. Interpretation of analytical data shows three major hydrochemical facies: Ca-HCO 3, Ca-Na-HCO 3 and Ca-Mg-Cl. The concentration of Ca 2+ and SO 42-is well within the desirable limit in all the locations. The SAR, RSC and Na% shows that most of the samples are suitable for irrigation. High values of TH and CR at many locations restrict its use for industrial purpose. © 2011 CAFET-INNOVA TECHNICAL SOCIETY. All rights reserved.